Implementasi Program CSR “Aku Baca” PT Gramedia Yogyakarta dalam Mendorong Minat Baca di DIY - Salsabila, Chairunisya Zulfa (Borobudur Communication Review, 2024)
This study aims to analyze the implementation of the Corporate Social Responsibility (CSR) program "Aku Baca" by PT Gramedia Yogyakarta in promoting reading interest among communities in the Special Region of Yogyakarta. The research background is based on Indonesia's low literacy levels, ranking 62nd out of 70 countries in the 2019 PISA survey. The study employs a qualitative descriptive approach with data collection through semi-structured interviews with the deputy manager of PT Gramedia Yogyakarta. The findings reveal that the "Aku Baca" program is implemented through a multi-stakeholder strategy involving schools, regional libraries, literacy communities, and local government. Implementation strategies include establishing reading corners in schools, training for teachers and educators, storytelling and creative literacy activities, and digital technology integration. The program also involves empowering local communities as literacy agents and providing continuous mentoring. Program evaluation shows significant improvements in reading corner visit frequency, participation in literacy activities, and positive changes in students' attitudes toward reading activities. Digital technology integration supports the development of digital literacy and students' critical thinking skills. This research provides theoretical and practical contributions to CSR program development in the literacy field and serves as a reference for companies and other stakeholders in designing innovative and sustainable literacy programs.